2017
DOI: 10.4314/ijbcs.v11i4.10
|View full text |Cite
|
Sign up to set email alerts
|

Approche ethnobotanique et ethnopharmacologique des plantes utilisées dans le traitement traditionnel de l’ulcère de Buruli à Akonolinga (Cameroun)

Abstract: Ethnopharmacological and ethnobotanical approach of medicinal plants used in the traditional treatment of Buruli ulcer in Akonolinga (Cameroon) ABSTRACTFew data are available concerning plants used in the traditional treatment of Buruli ulcer in Cameroon. This study aimed to identify species and characterize anti-Buruli ulcer recipes in the Akonolinga district. The H. N. BAYAGA et al. / Int. J. Biol. Chem. Sci. 11(4): 1523-1541, 2017 1524 ethnopharmacological survey has enabled to identify 25 plant species use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…We conducted a cross-sectional study from September 2017 to July 2018 in Akonolinga, the capital of Nyong et Mfoumou Division in the Centre Region of Cameroon. This division covers an area of 4,300 Km 2 approximately with a bit more than 100,000 inhabitants [6] . The climate is typically equatorial with two discontinuous dry and wet seasons.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a cross-sectional study from September 2017 to July 2018 in Akonolinga, the capital of Nyong et Mfoumou Division in the Centre Region of Cameroon. This division covers an area of 4,300 Km 2 approximately with a bit more than 100,000 inhabitants [6] . The climate is typically equatorial with two discontinuous dry and wet seasons.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the recipes collected in the maritime region consisted of at least two plant species. Several studies of traditional treatments for Buruli ulcer in Africa have highlighted this complexity in the preparation and content of remedies, which rarely include a single plant species (Bayaga et al, 2017). This form of association of various plant species in treatments or recipes could present risks of interaction or toxicity (Yemoa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Musa paradisiaca is also endowed with a good antimycobacterial activity with a beneficial interaction with several other plant species. Bayaga et al found in Cameroon that the plant was associated with 18 herbal recipes used in the fight against Buruli ulcer (Bayaga et al, 2017). Toxicity studies on most medicinal plants and interactions using animal models have provided results that strengthen their use among humans; however, many such plants could be associated with some toxicity (Nasri et al 2013, Yemoa et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Certaines espèces de la zone d'étude ont également fait l'objet de recherche par d'autres auteurs : Beunon 2011 Bayaga et al (2017) à Akonolinga (Cameroun) où ils rapportent que les feuilles de Sclerocarya birrea, Momordica charantia et Moringa oleifera y sont les plus utilisées par les tradithérapeutes. Dongock et al (2017) notent que les feuilles seraient fortement sollicitées par les traditherapeutes en raison de leurs richesses en substance actives.…”
Section: Discussionunclassified